Enfrentamento da violência sexual infanto-juvenil em Porto Alegre : contradições e perspectivas - Vieira, Monique Soares (2013)
The present study have as objective discuss about the materialization of actions to combat sexual violence against children and teens in scope the actions of the municipal government and its interface with Civil Society in the city of Porto Alegre / RS. In this sense, the research aimed to promote a critical contextualization about the municipalization the actions of the proposed National Plan for dealing with sexual violence against children and teens, aiming to strengthen the articulation between the municipal government and civil society to construction of public policies to guarantee rights of children and teens who are victims of violence. The specific objectives sought to analyze as it has been developed the actions aimed at combating sexual violence against children and teens; unravel how participatory spaces for civil society are organized, identify how the process of participation is encouraged and materialized in Porto Alegre, thus sought to know as is relationship between civil society and government, revealing how agents evaluate the process the combat with sexual violence. In view of the objectives proposed in this research, the type of search used outside of a qualitative approach, such as: the perceptions of individuals surveyed regarding the challenges and coping strategies of sexual violence against children and teens, the evaluation of these agents in the construction of such actions, the social relations that were established along the way of participation in the combat of sexual violence. The method chosen for analysis of reality was the critical-dialectical method using four categories historicity, totality, mediation and contradiction. To collect data, we used the desk research to analyze the Municipal Plans to Combat Sexual Violence Children and Teens (2012), and the Annual Reports of Accompaniments the children and adolescents the CREAS. To collect data, we used the desk research to analyze the Municipal Plan to Combat Sexual Violence Children and Youth (2012) of accompaniments to children and adolescents CREAS. In addition, use has been made of the interview, applying a form containing open questions with six subjects, who work in the process of coping with sexual violence in juvenile Porto Alegre (Child Protection Program of the Municipal Local Governance Reference Center for Victims of Violence of the Municipal Urban Security and Human Rights, Social Assistance Foundation, CMDCA and EVESCA). To analyze the data collected in the survey, it was decided by the technique of content analysis and the method of Systematization of Practice. The data analysis collected allowed the capture that way for materialization of coordinated actions between the Government and Civil Society in Porto Alegre necessitates the construction of strategies to able of ensure the fulfillment of rights of children and youth, given the complexity involved in the phenomenon, and expand and strengthen democratic participation of society in discussions and decision making.